Primary and secondary pre-service teachers’ attitudes towards inclusive education - Christopher Boyle; Chris Barrell; Kelly-Ann Allen; Long She (Heliyon, 2023)
The practice of inclusive education in schools has led to changes in policy and pedagogy, hence teacher acceptance and attitude are important components of its success. The aim of this study is to identify the differences in attitudes of primary and secondary pre-service teachers on inclusion and the potential relationship between demographic variables such as definitions of inclusion, previous experience working in a school, completion of a module on inclusive schools, and other variables. The study included 548 Australian university students studying primary (n = 348) or secondary (n = 193) professional teaching. All participants completed the Teacher Attitudes to Inclusion Scale (TAISA). Principle components analysis was performed to transform the TAISA questionnaire into smaller set of components and two-way between-groups analysis of variance was used to analyse data. Results showed that primary pre-service teachers have more positive attitudes towards inclusion than secondary pre-service teachers. Primary pre-service teachers were also more responsive to training on inclusive education. Implications for practice and future research are discussed.